Enterobacter Meningitis Due To Dermoid Cyst Manipulation: A Case Report - Rafiei Tabatabei, Sedigheh; Azma, Roxana; Kahbazi, Manigeh; Farzan, Abdonaser; Seifi, Kimia; Nahanmoghaddam, Negin Nahanmoghaddam (Iranian Journal of Child Neurology, 2018)
Gram-negative meningitis has been reported owing to dura-arachnoid barrier disruption. It can be occurred because of trauma, surgery and rarely infected dermoid cyst. In the 1940, for the first time, the association of neurosurgical procedures and meningitis due to gram-negative bacillary was described. Enterobacter is a serious infection with difficult treatment secondary to inability of many antibiotics to reach to adequate concentration in cerebrospinal fluid. Here in, we report a case of pediatric Enterobactermeningitis in a patient with manipulated dermoid cyst.She was cured with antibiotic therapy and surgery.